Performance evaluation of early maize genotypes in far western hills of Nepal - Prasai, Hari Kumar; Kushwaha, Ujjawal Kumar Singh; Joshi, Bishnu Prasad; Shrestha, Jiban (Journal of Maize Research and Development, 2015)
Initial evaluation trial of maize (early) genotypes was carried out at Regional Agricultural Research Station, Doti, Nepal in 2013 and 2014. Total fourteen and fifteen genotypes of early maize were included in initial evaluation experiment of the year 2013 and 2014 respectively. The experiment was laid out in randomized complete block design (RCBD) with three replications in each year. Out of the tested genotypes, SO3TEY/LN, ZM 423 and SO3TEY-FM (ER) identified as promising from statistical analysis over year. All the tested characters were found statistically significant. Similarly, the coordinated varietal trial of maize (early) was also carried out in the same station at 2013 and 2014. Total fourteen genotypes in 2013 and fifteen genotypes in 2015 of maize (early) were included in the experiment. The RCB design was applied and the experiment was replicated three times in every year. ZM 627 and ZM 621/Pool -15 genotypes identified as superior next to Arun-2 from the analysis of two year data. All the tested traits were found statistically significant in over year analysis. Journal of Maize Research and Development (2015) 1(1):106-111 DOI: http://dx.doi.org/10.5281/zenodo.34291